METHODOLOGICAL ISSUES IN COUNTERING CYBER TERRORISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article describes and discloses the methodological problems of counteringcyber terrorism, along with ensuring information security (hereinafter IS) in the activities of society, the state, and individual citizens. It also presents the main provisions, concepts and definitions,terms, methods of ensuring information security, various types and sources of information securitythreats, describes the organizational and legal methodological support of information security forthe activities of society and systems in various areas of its life cycle.At the same time, the use of high technologies at the same time imposes a high responsibility on the owners of information systems; without the proper level of security, it is impossibleto guarantee the confidentiality of entrusted and processed data. As you know, in the conditionsof active and large-scale introduction of information technologies in all areas of public administration, the urgency of this problem increases. At the same time, it is necessary to emphasize thatthe issues of ensuring information security and the problems of countering cyber terrorism havenot received a conceptual approach at the doctrinal and legislative level, although they are touchedupon in a number of some documents.
Keywords: methodology, information, information security, terrorism, cyber terrorism, anti-terrorist actions, international cooperation.